PENERAPAN ALGORITMA DJIKSTRA PADA PENCARIAN JALUR TERPENDEK - Ely Stya Arga; Gun Gun Firmansyah; Khairul Imam; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
The development of the times demands an effective and efficient method of activity. One of them is the method for determining the path. Dynamic human activities and being required to make displacement require a method that helps in determining the shortest path. Determining the shortest path has a reason to save fuel, time and power. One method that can be used for closest distance search is to use Dijkstra's algorithm. Dijkstra algorithm is an algorithm that applies a graph of direction and weight, where the distance between points is the weight of each arrow. This algorithm will look for the path with the minimum cost between one point and another. In addition, Dijkstra's algorithm can also be used to calculate the total cost or cost of the shortest trajectory that has been formed